Respuesta :
Answer with explanation:
We are asked to prove by the method of mathematical induction that:
[tex]2^n\leq 2^{n+1}-2^{n-1}-1[/tex]
where n is a positive integer.
- Let us take n=1
then we have:
[tex]2^1\leq 2^{1+1}-2^{1-1}-1\\\\i.e.\\\\2\leq 2^2-2^{0}-1\\\\i.e.\\2\leq 4-1-1\\\\i.e.\\\\2\leq 4-2\\\\i.e.\\\\2\leq 2[/tex]
Hence, the result is true for n=1.
- Let us assume that the result is true for n=k
i.e.
[tex]2^k\leq 2^{k+1}-2^{k-1}-1[/tex]
- Now, we have to prove the result for n=k+1
i.e.
To prove: [tex]2^{k+1}\leq 2^{(k+1)+1}-2^{(k+1)-1}-1[/tex]
Let us take n=k+1
Hence, we have:
[tex]2^{k+1}=2^k\cdot 2\\\\i.e.\\\\2^{k+1}\leq 2\cdot (2^{k+1}-2^{k-1}-1)[/tex]
( Since, the result was true for n=k )
Hence, we have:
[tex]2^{k+1}\leq 2^{k+1}\cdot 2-2^{k-1}\cdot 2-2\cdot 1\\\\i.e.\\\\2^{k+1}\leq 2^{(k+1)+1}-2^{k-1+1}-2\\\\i.e.\\\\2^{k+1}\leq 2^{(k+1)+1}-2^{(k+1)-1}-2[/tex]
Also, we know that:
[tex]-2<-1\\\\i.e.\\\\2^{(k+1)+1}-2^{(k+1)-1}-2<2^{(k+1)+1}-2^{(k+1)-1}-1[/tex]
(
Since, for n=k+1 being a positive integer we have:
[tex]2^{(k+1)+1}-2^{(k+1)-1}>0[/tex] )
Hence, we have finally,
[tex]2^{k+1}\leq 2^{(k+1)+1}-2^{(k+1)-1}-1[/tex]
Hence, the result holds true for n=k+1
Hence, we may infer that the result is true for all n belonging to positive integer.
i.e.
[tex]2^n\leq 2^{n+1}-2^{n-1}-1[/tex] where n is a positive integer.
Answer:
We rewrite the inequality as follows:
[tex]2^n \leq 2^{n+1} - 2^{n-1} - 1\\1 \leq 2^{n+1} - 2^{n} - 2^{n-1}\\1 \leq 4\cdot 2^{n-2} - 2 \cdot 2^{n-1} - 2^{n-1}\\1 \leq (4-2-1) \cdot 2^{n-2}\\1 \leq 2^{n-2}[/tex]
Which is true because n was given to be a positive integer.